Distributive Justice Analysis in the Context of Workers' Leave Time Regulation: A Legal Perspective - Robith Ainul Yaqin; Dipo Wahjoeono; Reinaldo Francisco Luis (Mimbar Keadilan, 2024)
The controversy surrounding Law No. 6/2023 revolves around the loss of the two-day weekend holiday entitlement for workers, the provision of only one day off in a six-day workweek, changes in working hours, which also affect rest time to only one day per week for a 6-day work schedule. The existence of a law should inherently provide fairness to society and contribute to the happiness of the people, but on the other hand, the government must also strive consistently to foster the economic growth of the population as a means to achieve social welfare. This research aims to investigate the regulation of workers' rest time under Law No. 6/2023 and to assess whether the provisions for rest time under Law No. 6/2023 have met the criteria of fairness for workers. To address these objectives, a normative juridical method with legislative and conceptual approaches is employed. Based on distributive justice theory, Law No. 13/2003 better reflects justice in labor relations in Indonesia as it considers basic needs, equality, and workers' contributions more comprehensively. Conversely, Law No. 6/2023, despite providing benefits to employers and potentially stimulating economic growth, appears to reduce the protection and welfare of workers, which can be deemed less fair according to distributive justice principles. Therefore, strict monitoring and improvements are necessary in the implementation of Law No. 6/2023 to ensure fairness for workers is maintained.